2021
DOI: 10.1017/jfm.2021.860
|View full text |Cite
|
Sign up to set email alerts
|

Shock induced aerobreakup of a droplet

Abstract: The multiscale dynamics of a shock–droplet interaction is crucial in understanding the atomisation of droplets due to external airflow. The interaction phenomena are classified into wave dynamics (stage I) and droplet breakup dynamics (stage II). Stage I involves the formation of different wave structures after an incident shock impacts the droplet surface. These waves momentarily change the droplet's ambient conditions, while in later times they are mainly influenced by shock-induced airflow. Stage II involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 63 publications
7
82
0
Order By: Relevance
“…Some models have proposed a mechanistic view of the breakup where it is assumed that surface instabilities play a major role in the atomization of droplets, particularly at high We. The 'Rayleigh-Taylor piercing' mechanism describes the rapid breakup of a flattened droplet by the penetration of surface waves generated on the windward face of the droplet due to rapid acceleration (Joseph, Beavers & Funada 2002;Theofanous & Li 2008;Sharma et al 2021). The Rayleigh-Taylor piercing mechanism has also been used to describe the breakup at low We, where it has been claimed to be the cause of the bag formation; however, recent works have called this into question, showing that the deformation rate is more strongly correlated to the breakup morphology and sizes at low We (Jackiw & Ashgriz 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some models have proposed a mechanistic view of the breakup where it is assumed that surface instabilities play a major role in the atomization of droplets, particularly at high We. The 'Rayleigh-Taylor piercing' mechanism describes the rapid breakup of a flattened droplet by the penetration of surface waves generated on the windward face of the droplet due to rapid acceleration (Joseph, Beavers & Funada 2002;Theofanous & Li 2008;Sharma et al 2021). The Rayleigh-Taylor piercing mechanism has also been used to describe the breakup at low We, where it has been claimed to be the cause of the bag formation; however, recent works have called this into question, showing that the deformation rate is more strongly correlated to the breakup morphology and sizes at low We (Jackiw & Ashgriz 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From (B2), we can obtain λ KH,1 < 0.1 mm in our experiment, indicating the possibility of the shear instability wave in the droplet length scale. Although the predicted wavelength of shear instability based on the KH limit underestimates the actual wavelength in many studies (Jalaal & Mehravaran 2014;Sharma et al 2021), we can still assume λ KH,1 d 0 based on the experimental observations, as shown in figure 6(a). The small-scale shear instability waves tend to cause local peeling on the droplet surface, or merge into a large liquid tongue.…”
Section: Discussionmentioning
confidence: 93%
“…2012; Jalaal & Mehravaran 2014; Sharma et al. 2021), especially those based on shock tube experiments, indicated that the early sheet originated from the KH instability wave on the surface of the droplet. The KH instability wave caused by the shear layer on the droplet surface was further stretched to form the sheet under the airflow action.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the physics of aerobreakup is crucial in designing and controlling these processes. Significant research has been already done to study the aerobreakup of Newtonian droplets, and they are well-reviewed in literature [5][6][7][8][9] . It is well established that the two most important dimensionless groups in the study of Newtonian droplet aerobreakup are Weber number (We) and Ohnesorge number (Oh), defined as…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in experimental facilities like high-speed cameras with better resolution, pulsed laser with nanosecond accuracy and Laser-induced fluorescence imaging technique etc. re-ignited the research in the field of aerobreakup 9,23 . The possibility of unifying Newtonian and non-Newtonian breakup modes under a single roof has been explored 21 .…”
Section: Introductionmentioning
confidence: 99%